Enhancing Students’ Creative Thinking Skills through the Process of Teaching Business Research - Wongpinunwatana, Nitaya (Journal of Management Policy and Practice, 2019)
The objective of this study is to propose a model for enhancing students’ creative thinking skills. This study collects data from 104 graduate students studying business research. A questionnaire relating to local thinking and collaboration was developed. Analytical thinking and creative thinking measurements were collected from graduate school entrance exam scores and instructors’ review of student’s research reports. The findings suggest that students’ logical thinking and collaboration directly affect analytical thinking and indirectly affect creative thinking via analytical thinking. In addition, students’ analytical thinking directly affects creative thinking. Participants in this research were students in one public university, so they may not be representative of students at other universities. Therefore, the effects of logical thinking, collaboration, and analytical thinking on creative thinking need to be investigated further. This research is one of only a few papers proposing a model for enhancing creative thinking. The model posits that logical thinking, analytical thinking and collaboration enhance creative thinking.